Предмет: Алгебра, автор: Мэрикейн

Помогите сосчитать:
1) 12 * (-√4) - 4* (-√4)^3 =
2) 12* √4 - 4* (√4)^3 =
3) 12* (-√2) - 4* (-√2)^3=
4) 12*√2 - 4* (√2)^3=

Ответы

Автор ответа: NNNLLL54
0
1); ; 12(-sqrt4)-4cdot (-sqrt4)^3=12cdot (-2)-4cdot (-2)^3=\\=-24-4cdot (-8)=-24+32=8\\2); ; 12sqrt4-4(sqrt4)^3=12cdot 2-4cdot 2^3=24-4cdot 8=24-32=-8\\3); ; 12(-sqrt2)-4(-sqrt2)^3=\\=[; ; (-sqrt2)^3=(-1)^3(sqrt2)^3=-1cdot (sqrt2)^2cdot sqrt2=-2sqrt2; ; ]=\\=-12sqrt2-4(-2sqrt2)=-12sqrt2+8sqrt2=-4sqrt2

4); ; 12sqrt2-4(sqrt2)^3=12sqrt2-4cdot (sqrt2)^2cdot sqrt2=\\=12sqrt2-4cdot 2cdot sqrt2=12sqrt2-8sqrt2=4sqrt2
Похожие вопросы
Предмет: Математика, автор: karpovad1989